Delineation of the Exact Transcription Termination Signal for Type 3 Polymerase III - Zongliang Gao; Elena Herrera-Carrillo; Ben Berkhout (Elsevier, 2018)
Type 3 Pol III promoters such as U6 are widely used for expression of small RNAs, including short hairpin RNA for RNAi applications and guide RNA in CRISPR genome-editing platforms. RNA polymerase III uses a T-stretch as termination signal, but the exact properties have not been thoroughly investigated. Here, we systematically measured the in vivo termination efficiency and the actual site of termination for different T-stretch signals in three commonly used human Pol III promoters (U6, 7SK, and H1). Both the termination efficiency and the actual termination site depend on the T-stretch signal. The T4 signal acts as minimal terminator, but full termination efficiency is reached only with a T-stretch of ≥6. The termination site within the T-stretch is quite heterogeneous, and consequently small RNAs have a variable U-tail of 1-6 nucleotides. We further report that such variable U-tails can have a significant negative effect on the functionality of the crRNA effector of the CRISPR-AsCpf1 system. We next improved these crRNAs by insertion of the HDV ribozyme to avoid U-tails. This study provides detailed design guidelines for small RNA expression cassettes based on Pol III.